2017
DOI: 10.1186/s12885-016-3037-z
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture combined with methylcobalamin for the treatment of chemotherapy-induced peripheral neuropathy in patients with multiple myeloma

Abstract: BackgroundChemotherapy-induced peripheral neuropathy (CIPN) seriously affects the quality of life of patients with multiple myeloma (MM) as well as the response rate to chemotherapy. Acupuncture has a potential role in the treatment of CIPN, but at present there have been no randomized clinical research studies to analyze the effectiveness of acupuncture for the treatment of CIPN, particularly in MM patients.MethodsThe MM patients (104 individuals) who met the inclusion criteria were randomly assigned into a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
121
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(127 citation statements)
references
References 31 publications
4
121
1
1
Order By: Relevance
“…Zhang et al 34 found electroacupuncture superior to acupuncture in terms of symptom relief and quality of life improvement in treating bortezomib-related neuropathy. Others found a positive effect for bortezomib-induced neuropathy 33,38,39 but a negative effect for taxane used for breast cancer. 32 Despite these findings, the limited number of studies prevents drawing any definite conclusions about the efficacy of acupuncture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al 34 found electroacupuncture superior to acupuncture in terms of symptom relief and quality of life improvement in treating bortezomib-related neuropathy. Others found a positive effect for bortezomib-induced neuropathy 33,38,39 but a negative effect for taxane used for breast cancer. 32 Despite these findings, the limited number of studies prevents drawing any definite conclusions about the efficacy of acupuncture.…”
Section: Discussionmentioning
confidence: 99%
“…The study selection flowchart is shown in Figure 1. Six RCTs were included: Molassiotis et al, 31 Greenlee et al, 32 Han et al, 33 Zhang et al, 34 Lu et al, 35 and Rostock et al 36 ; 5 of these were included in the meta-analysis. The characteristic and results of the included RCTs are presented in Table 1.…”
Section: Study and Data Extractionmentioning
confidence: 99%
“…One feasibility study with electroacupuncture in patients experiencing thalidomide or bortezomib‐induced peripheral neuropathy showed promising results which will need to be replicated in a randomized larger study . Several additional small trials have also investigated the benefits of neuropathy in CIPN due to various agents with inconsistent methodologies and results although it does appear that this intervention can be helpful to some patients . Additional therapeutic strategies are needed for the many cancer survivors who are living with CIPN worldwide.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Hastalarda periferal nöropati şiddeti ve ağrıda azalma görülürken, nöropatik fonksiyonlarda ve yaşam kalitesinde iyileşme olduğu bildirilmiştir. (20)(21)(22)(23)(24)…”
Section: Alternatif Tıp Sistemleri Akupunkturunclassified